Detection of minimal residual disease in NPM1-mutated acute myeloid leukemia by next-generation sequencing - Salipante, Stephen J. (2014)
Detection of minimal residual disease predicts adverse outcome in patients with acute myeloid leukemia. Currently, minimal residual disease may be detected by RQ-PCR or flow cytometry, both of which have practical and diagnostic limitations. Here, we describe a next-generation sequencing assay for minimal residual disease detection in NPM1-mutated acute myeloid leukemia, which encompasses ∼60% of patients with normal karyotype acute myeloid leukemia. Exon 12 of NPM1 was PCR amplified using sequencing adaptor-linked primers and deep sequenced to enable detection of low-prevalence, acute myeloid leukemia-specific activating mutations. We benchmarked our results against flow cytometry, the standard-of-care for acute myeloid leukemia minimal residual disease diagnosis at our institution. The performance of both approaches was evaluated using defined dilutions of an NPM1-mutation positive cell line and longitudinal clinical samples from acute myeloid leukemia patients. Using defined control material, we found this assay sensitive to approximately 0.001% mutant cells, outperforming flow cytometry by an order-of-magnitude. Next-generation sequencing was precise and semi-quantitative over 4 orders-of-magnitude. In 22 longitudinal samples from 6 acute myeloid leukemia patients, next-generation sequencing detected minimal residual disease in all samples deemed negative by flow cytometry. Further, in one-third of patients, sequencing detected alternate NPM1-mutations in addition to the patient's index mutation, consistent with tumor heterogeneity. Next-generation sequencing provides information without prior knowledge of NPM1 mutation subtype or validation of allele-specific probes as required for RQ-PCR assays, and without generation and interpretation of complex multi-dimensional flow cytometry data. This approach may complement current technologies to enhance patient-specific clinical decision-making.